EL EFECTO DE LAS NIIF EN EL GOBIERNO CORPORATIVO DE LAS CORPORACIONES PERUANAS - Tanaka, Gustavo (2020)
The purpose of this paper is primarily to analyze the effect of the mandatory implementation of IFRS in Peru on the accounting quality and subsequently, corporate governance (since transparency and comparibility in financial reporting and disclosure practice are primecorporate governance mechanisms to reduce the information asymmetry), and secondarily, to review the evolution of corporate governance and to suggest ways to improve the corporate governance situation in Peru. In order to reach those purposes, both primary andsecondary data were analyzed. Primary data were gathered through interviews to relevant stakeholders and surveys to non-financial listed companies. Secondary data were obtained from government official sources as well as databases like Osiris and Thomson.In order to complement the analysis of the impact of the mandatory adoption of IFRS, two studies were reviewed: earnings management and value relevance. The most important conclusion from this research is that the implementation of the IFRS has helped to improvethe quality of the accounting data and consequently, corporate governance, since before the adoption of the IFRS a not-well defined set of accounting standards was applied in Peru (a combination of tax rules and US GAAPs). Although a number of mechanisms have been implemented to improve the corporate governance in Peru, the situation is still incipient, a number of proposals are advanced,including the mandatory compliance of listed companies with the¨“Code of Good Corporate Governance for Peruvian Companies” and the corresponding penalties in case of no adherence to the principles.